PENGEMBANGAN APLIKASI LOCATION BASED SERVICE CAFE MENGGUNAKAN METODE ALGORITMA DIJKSTRA DAN HAVERSINE DI WILAYAH YOGYAKARTA BERBASIS ANDROID - Hanafi Eko Kurniawan; Erma Susanti; Suwanto Raharjo (Jurusan Informatika INSTITUT SAINS & TEKNOLOGI AKPRIND YOGYAKARTA, 2018)
The existence of cafe in metropolitan city has a role as place to relax and gather, Cafe is also needed by the city community itself as well as the newcomers. In this study discusses the use of applications as a medium to find information cafe combined with android-based mobile applications. The method used is a Location Based Service (LBS) using Dijsktra algorithm and Haversine methodsaccording to the user’s location is to get the location and the destination location sticks quickly and easily. This application has the main feature that is able to search for the nearest location in accordance with the current user’s location by using GPS (Global Positioning System) technology. With this application allows users or the general public who want to go to the café location without encountering obstacles.